Vestmann (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2018)
The works presented by Andrew Iacobucci is instinctively imbued in his Roman architectural education and has been particularly inspired by Steve Reich’s gradual musical processes. Such as Philip Glass and other minimalist musician. Their outcomes represent the challenge to decompose, analyze, shoot some of the signs, sequences or the series performed by the American musician and his musical heroes through rhythmic regroupings, metric modulations, etc.